Fa'āliyah al-Wasīlah al-Qiṣṣah al-Muqaṭṭa’iyyah ‘ala Taḥsīni Mahārah al-Kitābah laday aṭ-Ṭullab bi Madrasah al-Mutawassiṭah al-Islāmiyyah Miftāḥ al-Huda Demak: Efektivitas Media Strip Story Untuk Meningkatkan Mahārah al-Kitābah Siswa MTs Miftahul Huda Demak - Sabrina Ayu Salsabila; Amin Nasir (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
Students of MTs Miftahul Huda Jleper, Mijen, Demak experience difficulties and consider that learning Arabic is difficult and boring. This is because Arabic language learning at the school is still classified as using conventional media. To overcome this, used strip story media in the form of illustrated pieces of paper as a learning tool. This  aims to measure the effectiveness of strip story media to improve students' maharah kitabah. This research uses a quantitative research with a Nonequivalent Control Group method. The samples in class VIII A as an experimental class totaling 31 students and in class VIII B as a control class totaling 31 students. Data collection techniques are carried   out   by   conducting observation, test, and documentation. The data analysis techniques used in this study are descriptive analysis, normality test, homogeneity test, paired sample T-test, and independent sample T-test and N-Gain Test using the help of the SPSS version 22 program. The results of this research indicate that the use of media Strip Story effectively used as a learning media to improve maharah kitabah. This is evidenced by the results of the NGain Score and NGain percent tests in the experimental class. The N-Gain score was recorded at 0.7208, referring to the Meltzer g>0.7 category, which is in the high category. The results of N-Gain percent obtained a mean interval of 72.0777%, thus referring to the standard interpretation of the effectiveness of N-Gain (%) according to Hake is in the category quite effective. Keywords: Effectiveness, Learning Media, Mahārah al-Kitābah, Strip Story Media.